Technologies for Development From Innovation to Social Impact (Springer International Publishing, 2018)
This open access book presents 18 case studies that explore current scientific and technological efforts to address global development issues, such as poverty, from a holistic and interdisciplinary point of view, putting actual impacts at the centre of its analysis. It illustrates the use of technologies for development in various fields of research, such as humanitarian action, medical and information and communication technology, disaster risk-reduction technologies, habitat and sustainable access to energy. The authors discuss how innovative technologies, such as unmanned aerial vehicles for disaster risk reduction, crowdsourcing humanitarian data, online education and ICT-based medical technologies can have significant social impact. The book brings together the best papers of the 2016 International Conference on Technologies for Development at EPFL, Switzerland. The book explores how the gap between innovation in the global South and actual social impact can be bridged. It fosters exchange between engineers, other scientists, practitioners and policy makers active at the interface of innovation and technology and human, social, and economic development.